Barbarians and Christian Identity in the Corpus of Chromatius of Aquileia - Noce, Esteban Leopoldo (2017)
The article reflects on the image of the barbarians that Chromatius of Aquileia constructed and transmitted. It argues that the specific characteristics of the barbarians that emerge from Chromatius’ corpus do not bear any relation to the greater or lesser danger that the barbarians could have posed for the city in the first decade of the 5th century, as it has been sustained elsewhere, but rather that their presence was not relevant to the objective of the bishop’s preaching, which was to contribute to the consolidation of the unique Christian identity of his congregation.